Factors Affecting the Drop Out Rate of Family Planning Intrauterine Device: Hubungan Faktor-Faktor yang Mempengaruhi Drop Out Peserta Akseptor Keluarga Berencana IUD dengan Tingkat Kepatuhan - Mariana Afiati; Azhari Azhari; Firmansyah Basir; Theodorus Theodorus (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Objective: to assess the association between risk factors related to IUD acceptors' compliance at RSMH Palembang. Methods: This cross-sectional study was conducted in the Department of Obstetrics and Gynecology Dr. Mohammad Hoesin Hospital/Faculty of Medicine Sriwijaya University Palembang since May - December 2017. Subjects were women who use IUD contraceptives in the Department of Obstetrics and Gynecology Dr.MohammadHoesin Hospital Palembang and meet our inclusion and exclusion criteria. Medical counselling, knowledge, and side effects were assessed using a questionnaire. Data were analyzed by Chi-square test using SPSS software version 17. Results: There was a significant relationship between side effects and compliance of IUD use. There was no significant correlation between knowledge and medical counselling with compliance of IUD. Conclusions: Side effects associated with compliance of IUD. Keywords:compliance, contraception, IUD Abstrak Tujuan: mengetahui hubungan faktor-faktor resiko yang bermakna dalam mempengaruhi kepatuhan peserta akseptor IUD di RSMH Palembang. Metode: Penelitian potong lintang ini dilakukan di Departemen Obstetri dan Ginekologi Rumah Sakit Dr. Mohammad Hoesin/Fakultas Kedokteran Universitas Sriwijaya Palembang sejak Mei – Desember 2017. Sampel penelitian ini adalah perempuan yang menggunakan kontrasepsi IUD di Departemen Obstetri dan Ginekologi Rumah Sakit Dr. Mohammad Hoesin/Fakultas Kedokteran Universitas Sriwijaya Palembang dan memenuhi kriteria inklusi dan eksklusi. Konseling medik, pengetahuan, dan efek samping dinilai dengan menggunakan kuesioner. Data dianalisis dengan uji Chi square menggunakan SPSS versi 17. Hasil: Ada hubungan bermakna antara efek samping IUD dengan kepatuhan pemakaian IUD. Tidak ditemukan hubungan bermakna antara tingkat pengetahuan dan konseling medic dengan kepatuhan akseptor IUD. Kesimpulan: Efek samping IUD mempengaruhi kepatuhan pemakaian IUD. Kata kunci: IUD, kontrasepsi, kepatuhan.